Comparative Analysis of the Code of Ethics of the Accountant Profession in Terms of Religiosity in an Islamic Perspective - Ramadhani, Syefira; Ekasari, Kurnia; Dewi Sri Susilowati , Kartika (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to see, and contain values about ethics according to IAI and AAOFI, analyze accountant professional ethics from the point of view of religiosity, and find the formulation of accounting professional ethics according to Islam. Based on the purpose of this study, it is expected that a substitute for professional accounting ethics is not only by Islamic teachings, but also considered not representative balanced, fair, and honest as required by the accountant’s professional code of ethics. So that universal values, fairness, humanity, and flexibility will make accountant professional ethics acceptable to all groups, Muslims and non-Muslims. So, the professional ethics of Sharia accountants and conventional accountant ethics must be carried out by taking into account aspects of religiosity to prevent cases of violations of accounting ethics to provide benefits for all parties